Answer: option D is the correct answer.
Step-by-step explanation:
The given sequence is a geometric sequence because the consecutive terms differ by a common ratio.
The formula for determining the nth term of a geometric progression is expressed as
an = a1r^(n - 1)
Where
a1 represents the first term of the sequence.
r represents the common ratio.
n represents the number of terms.
From the information given,
a1 = 36
r = 12/36 = 4/12 = 1/3
Therefore, the formula for the nth term of the sequence is
an = 36 × 1/3^(n - 1)
an = 36 × 3^-1(n - 1)
an = 36 × 3^(-n + 1)
an = 36 × 3^(1 - n)
Answer:
y = 3/4x + 3
Step-by-step explanation:
you should only have y in one side and everything in other side of the equation. so you will first have -4y = -3x -12 , then you'll have to divide the right part of the equation by -4 . then you will have y = 3/4x + 3
Answer:
a) 13
Step-by-step explanation:
Answer:
2.1/1.5=7/n
Step-by-step explanation:
so easy